The Social Representations of Gifted Children in Childhood Professionals and the General Adult Population in France. (June 2022) - Sanchez, Christine; Brigaud, Emmanuelle; Moliner, Pascal; Blanc, Nathalie
This study explored the Social Representations (SRs) of Gifted Children in France, both in the general adult population and in different childhood professionals's populations (i.e., primary school teachers, secondary school teachers, and psychologists). Two binary SRs emerged from the data obtained from 608 participants. In the general population, the SR is "performative" and less diversified: gifted children were chiefly associated with exceptional intelligence. The "personological" SR of professionals indicated social, emotional, and behavioral characteristics. Few nuances distinguish the SRs of teachers from that of psychologists. This study highlights the need to better informed the general population and to better trained teachers and psychologists, to move towards a less stereotyped SR, congruent with the proven characteristics of gifted children.